Impact of the microcystic, elongated, and fragmented invasion pattern on prognosis in endometrial carcinoma: a comprehensive meta-analysis - Zhou, Li; Li, Chengyao; Zhao, Jianguo; Li, Pu; Qu, Pengpeng (Frontiers in Oncology, 2025)
The prognostic significance of the microcystic, elongated, and fragmented (MELF) invasion pattern in endometrial carcinoma (EC) has not been fully elucidated. This study conducted a systematic search across five electronic databases (PubMed, EMBASE, Cochrane, Web of Science, and the Chinese National Knowledge Infrastructure (CNKI)) from inception to April 2025. Assessment focused on overall survival (OS), disease-free survival (DFS), lymph node metastasis (LNM), and recurrence rate (RR) as primary outcomes. Meta-analysis calculations of overall odds ratios (ORs) and hazard ratios (HRs) with corresponding 95% confidence intervals (CIs) elucidated the impact of the MELF pattern on clinical outcomes. Analysis of 18 studies involving 5587 participants revealed a significant correlation between the presence of MELF pattern and heightened LNM incidence (OR 3.52, 95% CI: 2.17–5.71, p < 0.001). Univariate analysis indicated a notable inverse relationship between MELF pattern and OS (HR 2.31, 95% CI: 1.67–3.21, p < 0.001), as well as DFS (HR 1.67, 95% CI: 1.20–2.30, p = 0.002). In multivariate analysis, however, this association did not achieve statistical significance (for OS, HR 1.54, 95% CI: 0.99–2.41, p = 0.056; for DFS, HR 1.25, 95% CI: 0.90–1.74, p = 0.191). The findings of this meta-analysis demonstrated that the MELF pattern was linked to elevated risk of LNM and poorer OS and DFS outcomes. The correlation was influenced by various factors including surgical interventions and adjuvant therapies. While potentially increasing the risk of recurrence, the findings did not demonstrate statistical significance (OR 1.15, 95% CI: 0.61–2.16; p = 0.669).